2010
DOI: 10.1002/qj.544
|View full text |Cite
|
Sign up to set email alerts
|

The relation between airflow and orographic precipitation on the southern side of the Alps as revealed by weather radar

Abstract: The relative importance of various environmental parameters in determining orographic precipitation patterns in the Lago Maggiore region in the southern part of the European Alps is investigated. We examine 58 long-lasting and widespread orographic precipitation events corresponding in total to 106 days of rainfall. The mesoscale winds are estimated by means of Doppler velocity radar measurements; air-mass stability is computed from both radiosoundings and pairs of ground stations located at different heights.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 32 publications
5
64
0
1
Order By: Relevance
“…in the Graubünden region in the east of Switzerland where substantial blocking of precipitation is observed, and Lugano (LUG, 273 m a.s.l.) in the Tessin region to the south of the main Alpine divide which is significantly affected by Mediterranean weather patterns and orographic forcing, especially in the summer and fall seasons (Panziera and Germann, 2010). Schüepp and Gensler (1980).…”
Section: Meteorological Data and Study Sitesmentioning
confidence: 99%
“…in the Graubünden region in the east of Switzerland where substantial blocking of precipitation is observed, and Lugano (LUG, 273 m a.s.l.) in the Tessin region to the south of the main Alpine divide which is significantly affected by Mediterranean weather patterns and orographic forcing, especially in the summer and fall seasons (Panziera and Germann, 2010). Schüepp and Gensler (1980).…”
Section: Meteorological Data and Study Sitesmentioning
confidence: 99%
“…As precipitation in mountainous regions is influenced by orographic forcing, Panziera and Germann (2010) investigated the effects of orographic forcing on the rainfall patterns in the Lago Maggiore Region in southern Switzerland (Fig. 1).…”
Section: Nora -Nowcasting Of Orographic Rainfall By Means Of Analoguesmentioning
confidence: 99%
“…Since the orographic forcing dominates the patterns of rainfall in the mountains (e.g. Houze et al, 2001;Panziera and Germann, 2010;Yuter et al, 2011), it can be exploited for nowcasting of precipitation. NORA takes advantage of not only the effects of the orographic forcing, but also the recent improvements of the Swiss weather radar precipitation estimates (Germann et al, 2006).…”
Section: Outline Of This Articlementioning
confidence: 99%
“…In Panziera and Germann (2010), from now on PG10, we analysed a large number of long-lasting orographic precipitation events occurring over the Lago Maggiore region, which is located in the southern part of the European Alps between Italy and Switzerland (Figure 1). In PG10 we demonstrated that the orographic forcing gives repeatability to the rainfall patterns observed in the mountains with certain environmental conditions.…”
Section: The Concept Of Noramentioning
confidence: 99%